The Impact of Water Storage on Microleakage of Two Generations of Dentin Bonding Agents: An In-Vitro Study - Agha Mohammadi, Zahra (Journal of Dental School, 2024)
Objectives The latest generation of bonding agents is increasingly embraced and well-suited to fulfilling the requirements for durable restorations. This study aimed to assess microleakage levels of three self-etch adhesives (Clearfil SE (SE), Protect (PB), and Tri-S (TS) Bonds) in composite restorations at both occlusal and cervical borders, while considering the impact of water storage over different time intervals. Methods Standard Class V cavities were prepared on buccal surfaces of 84 human premolars at the level of cementoenamel junction. The samples were randomly assigned to six groups (N=14). The corresponding bonding procedure in each group was completed, and the cavities were filled using Clearfil AP-X (Kuraray). Following thermocycling, the teeth were stored in deionized water within an incubator for 24-hour and 6-month intervals. Statistical analysis of microleakage data was conducted utilizing Kruskal-Wallis and Mann-Whitney U tests at p<0.05. Results Following a 24-hour interval, the level of microleakage at the occlusal surface was greater than the gingival surface for SE. No statistically significant differences were observed in microleakage at the occlusal and cervical borders after 24h of water storage for the PB and TS groups (P=0.51, 0.16). None of the SE and TS group samples showed leakage at the occlusal or cervical margins following a 6-month interval. Conclusion Self-etching bonding agents indicated increased occlusal microleakage compared to the cervical margin microleakage.